D. N. Rodowick: An Education in Judgment. Hannah Arendt and the Humanities, Chicago: UCP, 2021.: Rodowick. D. N., An Education in Judgment: Hannah Arendt and the Humanities. Chicago University Press 2021, 182 p., 34.39 EUR. - Gardiner, Rita A. (HannahArendt.net, 2022)
In this short and elegantly written book, the philosopher D. N. Rodowick lays out reasons why Hannah Arendt’s writings can revitalize ideas about the importance of philosophical thinking and reasoning to the humanities. The book consists of a preface and six interconnected essays. The essay form was one that Arendt was also fond of, as her favourite collection of her own writings, Between Past and Future, illustrates. So it was good to see someone adopting this style of writing in a full-length monograph. What I liked most about this finely-argued book was the author’s concentration on some of Arendt’s lesser-studied works. There is a close reading of her essay “The Crisis of Culture,” a particular favourite of mine. Rodowick maintains that this essay sums up some of Arendt’s main arguments in The Human Condition. As well, as discussing her lectures on Kant, we have a thoughtful reading of her lecture on “Philosophy and Politics”, which shows her engagement with Platonic and Socratic thought. This concentration on some of Arendt’s lesser-known works is a strength of this collection.